Cytotoxicity, Antimicrobial, and In Silico Studies of Secondary Metabolites From Aspergillus sp. Isolated From Tecoma stans (L.) Juss. Ex Kunth Leaves - Elsayed, Heba E.; Kamel, Reem A.; Ibrahim, Reham R.; Abdel-Razek, Ahmed S.; Shaaban, Mohamed A.; Frese, Marcel; Sewald, Norbert; Ebrahim, Hassan Y.; Moharram, Fatma A. (Frontiers in Chemistry, 2021)
Endophytes are prolific producers of privileged secondary metabolites with diverse therapeutic potential, although their anticancer and antimicrobial potential still have a room for further investigation. Herein, seven known secondary metabolites namely, arugosin C (1), ergosterol (2), iso-emericellin (3), sterigmatocystin (4), dihydrosterigmatocystin (5), versicolorin B (6), and diorcinol (7) were isolated from the rice culture of Aspergillus sp. retrieved from Tecoma stans (L.) Juss. ex Kunth leaves. Their anticancer and antimicrobial activities were evaluated in MTT and agar well diffusion assays, respectively. The cytotoxicity results showed that metabolite 3 displayed the best viability inhibition on the MCF-7 breast cancer cells with IC50 = 225.21 µM, while 5 on the HepG2 hepatocellular carcinoma cells with IC50 = 161.81 µM. 5 demonstrated a 60% apoptotic mode of cell death which is virtually correlated to its high docking affinity to Hsp90 ATP binding cleft (binding score −8.4 Kcal/mol). On the other side, metabolites 4 and 5 displayed promising antimicrobial activity especially on Pseudomonas aeruginosa with MIC = 125 μg/ml. The observed effect may be likely related to their excellent in silico inhibition of the bacterial DNA-gyrase kinase domain (binding score −10.28 Kcal/mol). To the best of our knowledge, this study is the first to report the promising cytotoxic and antibacterial activities of metabolites 3, 4, and 5 which needs further investigation and renovation to therapeutic leads.